Association of Extracranial Carotid Artery Stenosis in Ischemic Stroke in a Sri Lankan Cohort of Patients - An Analytical Cross-Sectional Study - Rajapakshe (MBBS, MD, MRCP), Ishani; Wijesundara (MBBS), Devasmitha; Chandrakumara (MBBS, MD), Amila; Senanayake (MBBS, MD, FRCP, FCCP), Bimsara (International Journal of Innovative Research in Medical Science, 2022)
Background and Objectives: The burden of stroke in Sri Lanka is on the increase with the current demographic transition toward an ageing population. However, the association of symptomatic extracranial carotid artery stenosis (CAS) in ischemic stroke has not been prospectively evaluated in a Sri Lankan cohort of ischemic stroke patients. Globally population-based studies have estimated about 15% of ischemic strokes are caused by large vessel occlusions. It is commonly believed that the prevalence of significant extracranial CAS is low in Sri Lanka compared to western populations. The purpose our study is to systematically analyses and assess this long held notion and to search for other associated causative factors. Methods: The study population comprised of 164 acute ischemic stroke patients admitted consecutively to the National hospital of Sri Lanka over a period of 3 months. Carotid artery duplex scans were done by a single well-trained operator within 2 weeks of presentation and degree of CAS was classified as low (<50%), moderate (50-69%), severe (>70%) and complete occlusion according to NASCET criteria. Factors associated with CAS were identified by stepwise multiple logistic regression analysis. Results: Out of 164 ischemic stroke patients 104 (63.4%) were male and 60 (36.6%) were female. The mean age of stroke patients was 62.2+- 14.21 years. 139 (84.8%) had low grade stenosis, 10 (6.1%) had moderate stenosis, 7 (4.2%) had severe stenosis and 8 (4.9 %) had complete stenosis of carotid artery. Older age and presence of previous TIAs were significantly associated with CAS. Gender, hypertension, diabetes mellitus, hypercholesterolemia, IHD, previous stroke, previous TIA, previous use of antiplatelets, family history of stroke, previous use of statins and presence of carotid bruit were not significantly associated. Conclusion: Extracranial carotid artery occlusion previously considered a rare cause of ischemic stroke in Sri Lanka was found to be having prevalence similar to western populations in this study with over 15% having significant stenosis. Hence, we emphasize that early carotid doppler studies must be performed in all ischemic strokes at least within two weeks and necessary interventions carried out where it is deemed necessary.